Shear bond strength of composite resin to biodentine after different surface treatment (Mustansiria Dental Journal, 2023)
Aim of the study: The study's objective was to assess the shear bond strength (SBS) between composite and Biodentine after applying various treatments of the surface for the roughness of the latter material.Materials and Methods: Four groups of forty Biodentine samples were created by mixing the material according to the manufacturer's instructions and inserting it into plastic cylinders that were 3 mm in diameter and 2 mm in height, respectively. Group (1) was the control group without surface roughness of samples, Group (2) roughness treatment of the surface with thirty-seven percent of orthophosphoric acid, Group (3) roughness treatment of the surface by abrasion method with air by using aluminum oxide (Al203) elements, and Group (4) roughness treatment of the surface with 9% hydrofluoric acid.  Over the samples of groups (2, 3, and 4), a universal adhesive bonding agent was applied, curing the bond. Each sample was covered by fresh cylinders that measured 3 mm in diameter and 6 mm in height, respectively. A composite was then added in two layers, with 3 mm between each layer, and light-cured. After cutting and removing the plastic cylinders to acquire the two materials bound together as one block,      a universal testing machine was used to evaluate the failure load between Biodentine and composite for all samples. Data analysis using the Duncan multiple range test and One-Way ANOVA.       Results: SBS (Shear Bond Strength) between groups was found to differ significantly (P≤0.05). Except for Gp(2) and Gp(3), which revealed no significant difference between the two groups, the largest and lowest SBS were related to Groups (2) and (1), respectively.